Efeitos de um exercício de AVD na configuração toracoabdominal pela pletismografia opticoeletronica e hiperinsuflação em pacientes com DPOC - Capeletti, Aldenice Magalhães (2018)
Introduction: Exercise limitation is a major cause of disability in patients with Chronic Obstructive Pulmonary Disease (COPD) and is largely the result of disturbances in respiratory mechanics. The volume change is distributed between thoracic wall (TW) both upper, lower and abdominal compartments difficult to observe by conventional spirometric methods. Electronic Optical Plethysmography (POE) is a non-invasive and accurate method to measure the total volume and percentage of contribution of these compartments in respiratory movements. Aim: To evaluate, through POE and Spirometry, the contribution of , upper thoracic compartment (UTC) lowe thoracic compartment (LTC) and abdomen (ABD) respiratory movements of patients with COPD, before and after daily life activity (DLA) exercises. Materials and Methods: A cross-sectional study involving 25 patients with mild and moderate COPD, with 61.9 ± 10.8 gonads, both of whom were submitted to adapted TGlittre-DLA. They were evaluated by spirometry and POE, pre and post DLA. Results: The main results obtained after DLA the main results of the study obtained after AVD were increased LV * p = 0.005 and ABD percentage p = 0.054 * and CTS decrease p = 0.008 *, IC reduction p = 0.040 * and increase of VRE p = 0.006 *. Conclusion: it was concluded that there was a change in the thoracoabdominal kinetics, mainly on the percentage of abdominal compartment contribution and dynamic hyperinflation (DH), as an acute effect after physical exercise of LDA.